(untitled) (International Journal of Medical and Surgical Sciences, 2021)
Endothelial dysfunction as well as hypercoagulability have been described as the initial triggers of atherosclerosis and cardiovascular damage and have been associated with subclinical hypothyroidism (SHC). The aim of this research was to determine the concentration of nitric oxide (NO), fibrinogen and circulating lipids in patients with subclinical hypothyroidism and to correlate these variables with thyrotropin (TSH) concentration to establish their possible association with the development of cardiovascular damage. A descriptive, cross-sectional, correlational study was conducted at the IESS Hospital in Riobamba, Ecuador, in the period from January 2019 to September 2021. Ninety-five subjects were studied (65 patients with CAH and 30 controls). The concentration of total cholesterol, triglycerides, HDL cholesterol and LDL cholesterol, TSH, free thyroxine, ON and fibrinogen were determined. Results: We found a decrease in the concentration of ON (p<0.001), accompanied by an increase in the concentration of total cholesterol (p<0.0001), LDL cholesterol (p<0.01) and fibrinogen (p<0.0001) in patients with CAH vs. controls. A negative correlation (p<0.0001; r= -0.5020) was observed between TSH and ON and a positive correlation (p<0.0001; r= 5412) between TSH and plasma fibrinogen in patients with CAH. Conclusion: patients with CAH showed a decrease in serum ON levels and an elevation in plasma fibrinogen concentration. Both measurements correlated significantly with TSH concentration. These parameters associated with an increase in total cholesterol and LDL cholesterol could favor vascular dysfunction, the development of atherosclerosis and consequent cardiovascular damage.